Nanofluid flow and heat transfer between a stationary nonpermeable disk and a permeable rotating shrinking disk with radiation and heat generation effects - Yahaya, Rusya Iryanti; Md Arifin, Norihan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Semarak Ilmu Publishing, 2023)
The flow between bounded surfaces is known as internal flow. The internal flow between disks has many significant applications, such as gas turbine rotors, rotating machinery, food processing technology, and air cleaning machines. In the current study, the nanofluid flow between two disks, nonpermeable and stationary, and the other permeable, rotating and shrinking, is analysed. The governing partial differential equations and boundary conditions are proposed with the inclusion of radiation and heat generation effects. Then, similarity transformations are utilised in deriving the nonlinear ordinary differential equations and boundary conditions for computation using the bvp4c solver. Multiple solutions are obtained, and only the first solution is stable. The combination Mn-ZnFe2O4/C2H6O2 nanofluid is found to produce the lowest magnitude of skin friction coefficient and the highest heat transfer rate.